FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PENYELENGGARA PELAYANAN PUBLIK PEMERINTAH KOTA BATAM - Puspitasari, Meri Enita; Setyobudi, Yustinus Farid; Pratiwi, Diah Ayu (JURNAL DIMENSI, 2015)
This research entitled Factors Affecting Compliance Implementation of Public Service Government of Batam. This study aims to determine the factors that influence the level of compliance of public service providers in the City of Batam. This research is useful to provide recommendations solutions and strategies to improve adherence public service providers.This research is a qualitative descriptive study. This study took place at the Department of Health and Department of Education Batam. The variables of this study were (1) Factors compliance behavior as independent variables, (2) Compliance with the Public Service Operator in accordance with Law No. 25 About the Public Service as the dependent variable. Data collection techniques with observation, interviews and documentation and questionnaires as secondary data. This research data analysis techniques using analysis of data reduction, data presentation and conclusion / verification.Results of this study based on behavioral factors, namely compliance in providing services to the public, the Department of Education and the Health Department in the knowledge, attitudes and actions in providing the services referred to Batam City Government Regional Regulation No. 1 Year 2014 on the Implementation of Public Service. While in service execution factors that in the implementation of the service to the community, the Department of Education and Department of Health have conducted according to the standards of service prescribed by the Government of Batam in accordance with Regulation No. 1 Year 2014 area Implementation of services carried out can be seen that the start of the awareness factor, organizational factors, factors rule, factor income, capabilities and skills, as well as service facilities factor, getting a response different from service users (community). Of the six factors are used as indicators of the implementation of services in this study, the factors factor rules and service facilities are under the spotlight of the public. Based on observations and interviews conducted are still many people who complained about how far the service provider to provide services not in accordance with service standards are displayed in the object of research.      Conclusion The research is Factors compliance behavior: In providing service to the community, required the Department of Education and Department of health knowledge,attitudes and actions in providing the services referred to Batam City Government Regional Regulation No. 1 Year 2014 on the Implementation of Public Service. But the results of this research that the compliance behavior factor still does not work as mandated by the Act. And Factor implementation of the service: In the implementation of service to the community, the Department of Education and Department of Health have conducted according to the standards of service prescribed by the Government of Batam in accordance with Regional Regulation No. 1 Year 2014. Implementation of services carried out can be seen that the factors of consciousness, organization, rules, income, ability and skills, as well as service facilities, got a different response from the service users (community). Of the six factors are used as indicators of the implementation of services in this study, the factors factor rules and service facilities are under the spotlight of the public. Based on observations and interviews conducted are still many people who complained about how far the service provider to provide services not in accordance with service standards are displayed in the object of research.